Letter - Morgan, Betty
1939-08-02 038-0076-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 30, ECCLESTON STREET, LONDON, S.W.1. TELEPHONE: SLOANE 9866 HVT/FC/681. 2nd August, 1939. H.V. Tewson, Esq., Transport House, Smith Square, S.W.1. Dear Mr. Tewson, I enclose copy of a letter which I have just written to Mr. Leaker. Yours sincerely, Betty Morgan Organizing Secretary. Encl. 292/946/38/76(I)